Effects of Astragalus injection and Salvia Miltiorrhiza injection on serum inflammatory markers in patients with stable coronary heart disease: a randomized controlled trial protocol - Luo, Zhihao (Trials, 2020)
BACKGROUND: Coronary heart disease (CHD) is a clinical syndrome caused by coronary atherosclerosis (AS) or functional changes in coronary arteries. We have previously reported that astragaloside IV (in astragalus) and tanshinone IIA (in Salvia miltiorrhiza) improve myocardial ischemic injury. METHODS: This study will employ the randomized, blinded, prospective, single-center experiments approach. Briefly, a total of 160 eligible patients will be equally randomized into three treatment groups and placebo control groups. Patients will receive appropriate treatments every 24 h for seven days after enrollment and followed up for 28 days. The main evaluation indicators will be cell count, serum high-sensitivity C-reactive protein (hs-CRP) level, monocyte chemoattractant protein 1 (MCP-1), interleukin-6 (IL-6), interleukin-1β (IL-1β), interleukin-8 (IL-8), interleukin-18 (IL-18), interleukin-10 (IL-10), tumor necrosis factor (TNF)-α, oxidized low density lipoprotein (OX-LDL), angina grade, and Traditional Chinese Medicine (TCM) symptom changes scale. Secondary indicators to be evaluated will include B-type natriuretic peptide (BNP) levels, troponin (cTn), muscle enzyme isoenzyme (CK-MB), heart-type fatty acid binding protein (H-FABP), liver and renal functions, as well as blood coagulation. Close monitoring of adverse events during the trial will also be conducted. DISCUSSION: This randomized controlled trial of Chinese herbal extracts for the treatment of coronary heart disease will generate results that are expected to provide valuable clinical evidence to inform future development of therapies towards management of CHD. TRIAL REGISTRATION: China Clinical Trial Registration Center, ChiCTR1900021590. Registered on 28 February 2019.